Epidemiological and clinical profiles of cutaneous leishmaniasis cases in Amhara National Regional State, Northwest Ethiopia: a multicenter retrospective study - Bizuayehu Gashaw; Endalew Yizengaw; Endalkachew Nibret; Addisu Workineh; Adisu Abebe (PAGEPress Publications, 2024)
Cutaneous leishmaniasis (CL) is caused by Leishmania parasites. Ethiopia is one of the top ten countries with high CL load. Amhara National Regional State (ANRS) is one of the CL hotspot areas in Ethiopia. This study determined the epidemiology and clinical profiles of CL in ANRS. This study was conducted from April to October 2023 in eight Leishmaniasis Treatment Centres (LTCs). A data review was done from patients presenting to these centres between June 2018 and July 2023. Chi-square test and logistic regression were performed using SPSS-23. A total of 1729 CL patients were recorded. The overall burden of CL per 10,000 outpatients was 900. Most of the patients (71.1%) presented with localised cutaneous leishmaniasis (LCL). The patients were from 112 districts. About 12% of the patients lived with the disease for over a year without treatment. Multiple-time comer patients accounted for 13.2% of the patients. Cutaneous leishmaniasis is still a major public health problem in ANRS. One-third of CL patients presented with the MCL clinical form. There was longer delay among CL patients for seeking diagnosis and treatment. Large scale community based study and traditional and modern treatment centers focused studies should be included to estimate the actual number of CL in the region. Follow-up and molecular studies are important to better understand the clinical features of the disease.  Moreover, awareness of the community about the CL prevention and control help the patients to get early diagnosis and treatment.